A Study On Sleep Disturbance And Associated Factor Among Manufacturing Workers In Johor - Nur’ Aishah Izzaty, Abd Hamid (2025)
Sleep disturbances are a significant occupational health issue among factory workers due to unpredictable schedules, long hours, and high stress levels. This study evaluates the prevalence and factors contributing to sleep disturbances among industrial workers in an electronic manufacturing facility in Johor, Malaysia. Data were collected from 66 operational workers using self-administered questionnaires. Validated instruments, including the Sleep Quality Scale (SQS), Work Stress Questionnaire (WSQ), and Health and Work Performance Questionnaire (HPQ), assessed sleep quality, work stress, and job performance. The findings revealed that 60.6% of respondents experienced moderate sleep disturbances, 37.9% reported minor disturbances, and 1.5% faced severe issues. Shift work and occupational stress were identified as key contributors to poor sleep quality, significantly affecting job performance and emphasizing the critical role of sleep in maintaining workplace efficiency and safety. Workers exposed to moderate levels of shift work and stress were particularly prone to significant sleep disruptions. Despite its valuable contributions, the study faced limitations, including a small sample size, geographic focus on Johor, and reliance on self-reported data, which could introduce reporting biases and limit generalizability. Nonetheless, it highlights the intricate link between workplace demands and sleep patterns in the manufacturing sector. The study underscores the need for employers to prioritize strategies to mitigate sleep disturbances, such as workplace wellness initiatives, shift pattern adjustments, and stress management programs. Future research should expand across industries and regions, adopt longitudinal designs to explore causal relationships, and evaluate targeted interventions. Addressing workplace sleep issues can enhance employee well-being, operational safety, and overall productivity, benefiting both workers and organizations.